Nanobodies: a promising approach to treatment of viral diseases - Minatel, Vitória Meneghetti; Prudencio, Carlos Roberto; Barraviera, Benedito; Ferreira, Rui Seabra (Frontiers in Immunology, 2024)
Since their discovery in the 1990s, heavy chain antibodies have garnered significant interest in the scientific community. These antibodies, found in camelids such as llamas and alpacas, exhibit distinct characteristics from conventional antibodies due to the absence of a light chain in their structure. Furthermore, they possess a single antigen-binding domain known as VHH or Nanobody (Nb). With a small size of approximately 15 kDa, these Nbs demonstrate improved characteristics compared to conventional antibodies, including greater physicochemical stability and enhanced biodistribution, enabling them to bind inaccessible epitopes more effectively. As a result, Nbs have found numerous applications in various medical and veterinary fields, particularly in diagnostics and therapeutics. Advances in biotechnology have made the production of recombinant antibodies feasible and compatible with large-scale manufacturing. Through the construction of immune phage libraries that display VHHs and subsequent selection through biopanning, it has become possible to isolate specific Nbs targeting pharmaceutical targets of interest, such as viruses. This review describes the processes involved in nanobody production, from hyperimmunization to purification, with the aim of their application in the pharmaceutical industry.